Aortic root remodeling with external annuloplasty for acute type A aortic dissection: Midterm results. Issue 5 (8th October 2020) - Morgant, Marie‐Catherine; Malapert, Ghislain; Bernard, Chloé; Laubriet, Aline; Pujos, Charline; Varin, Thomas; Lansac, Emmanuel; Bouchot, Olivier
Abstract: Background: To evaluate the role of aortic root remodeling with external aortic annuloplasty (ARREAA) in acute type A aortic dissection (AAAD). Methods: From May 2011 to May 2020, 59 patients out of 240 with AAAD underwent ARREAA. Data were retrospectively collected and analyzed. Results: The mean age was 61.4 ± 8.6 years and 43 patients were males (73%). Hemiarch and total arch replacement were performed in 37 (62.7%) and 14 (23.7%) patients. An aortic valvuloplasty was performed in seven patients (11.8%). Five patients (8.5%) required coronary artery bypass graft. Re‐exploration for bleeding was required in six patients (10.1%). The 30‐day mortality rate was 18.6%. Preoperative hemodynamic instability (odds ratio [OR] = 8.57, 95% confidence interval [CI] = 1.57–46.71; p = 0.013), consciousness disorder (OR = 19.18, 95% CI = 3.02–121.72]; p = 0.002) or myocardial ischemia (OR = 6.28, 95% CI = 1.27–31.10; p = 0.013) were significantly associated with postoperative mortality. No patient was reoperated for aortic valve during the postoperative period. One patient suffered a stroke postoperatively with partial recovery. Kidney failure requiring temporary dialysis occurred in 12 patients (20.3%). At discharge, a transthoracic echocardiogram showed moderate aortic regurgitation (AR; grade 2) in two patients. During follow‐up (mean = 58.4 ± 32.4 months), three patients died. The rate of mortality was 6.2%. Actuarial survival at 5 years was 76.3%. No patient required reoperation on the proximal aorta or aortic valve. At 4 years, freedom from any aortic valve or root reintervention and AR > 2 were both 100%. Conclusion: In a center with expertise in valve‐sparing procedures, ARREAA is a reasonable option in the surgical management of AAAD in selected patients. This technique stabilizes the aortic annulus and preserves root anatomy for durable outcomes.